Philosopher kings? the adjudication of conflicting human rights and social values - Christie, George C. (New York ; Oxford : Oxford University Press, 2011)
'Philosopher Kings' examines the attempts by courts to sort out conflicts involving freedom of expression, including religious expression on the one hand and rights to privacy and other important social values on the other.
Includes bibliographical references and index.
Keywords: Human rights -- Cases